Simultaneous analysis of acylcarnitines using MALDI-TOF mass spectrometry based on a parylene matrix chip - Noh, Joo-Yoon; Kim, Moon-Ju; Yun, Tae Gyeong; Kang, Min-Jung; Pyun, Jae-Chul (Royal Society of Chemistry, 2022)
Short and medium chain acylcarnitines have been used for the diagnosis of various fatty acid oxidation and organic acid disorders. This report presents a multiplex and quantitative analysis of acylcarnitines using MALDI-TOF MS based on a parylene matrix chip. The parylene matrix chip was fabricated by the deposition of a nanoporous film of parylene on an organic matrix array, which reduced the number of mass peaks from the organic matrix in the low m/z range. Quantitative analysis was possible using the parylene matrix chip because of the formation of nano-sized sample crystals on the nanoporous parylene film. Seven acylcarnitines were quantitatively analyzed using the chip; the method detection range included the cut-off values for metabolic disorders. The seven acylcarnitines of different concentrations were simultaneously detected using the parylene matrix chip and the interference from the mixed carnitines was estimated. Real l-carnitine (C0) samples were analyzed using serial dilution, and the recoveries were calculated by comparisons with a standard curve.